STRENGTHENING STUDY PROGRAM DISTINCTION THROUGH HALAL LOCAL PRODUCT-BASED EXTRACURRICULAR ACTIVITIES - Hendrianto Hendrianto; Lutfielfalahy Jamin; Amrullah Amrullah; Eyen Tika Sari (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2026)
An This study analyzes the implementation of extracurricular activities among students of the Sharia Economic Law Study Program and the sharpening of its academic distinction through strengthening contemporary issues, such as the halal status of local products, as part of the practical application of Islamic economic principles. This research is field research using a descriptive qualitative approach. The primary data sources include the head and secretary of the Sharia Economic Law Study Program, lecturers supervising extracurricular activities, and 25 students who are members of the Student Association of the Sharia Economic Law Study Program. Secondary data were obtained from relevant documents, such as guidelines for student activities. Data collection techniques consisted of observation, interviews, and documentation. The data analysis process involved preparing and organizing the data, reading all data thoroughly, coding the data, applying coding to describe the research setting, participants, categories, and themes, presenting the themes in qualitative narratives, and interpreting the findings. The results show that extracurricular activities in the Sharia Economic Law Study Program include moot court simulations, debates, and interactive discussions with experts. However, scheduling conflicts often pose challenges. The implementation of these activities is also integrated with educational issues related to the halal status of local products. Furthermore, the design of extracurricular programs helps strengthen the program’s academic distinction by integrating local wisdom into Islamic-based economic empowerment activities, such as small and medium enterprise (SME) development programs focusing on halal local products.